Targeting the lateral but not the third ventricle induces bone loss in ewe: an experimental approach to generate an improved large animal model of osteoporosis - Oheim, Ralf; Egermann, Marcus (The journal of trauma and acute care surgery, 2012)
Osteoporosis is a chronic disease characterized by bone loss and increased skeletal fragility. Large animal models are required for preclinical testing of new therapeutic approaches. We have recently demonstrated that continuous intracerebroventricular (ICV) application of leptin into the lateral ventricle (LV) induces bone loss in ewe. On the basis of these findings, we reasoned that the third ventricle (TV) is an even better target because of its closer location to the hypothalamus that mediates leptin effects on bone.